Novice nurses’ professional competence: A qualitative content analysis - Zahra Mehri; Ladan Zarshenas; Mahnaz Rakhshan; Zahra Khademian; Manoosh Mehrabi; Zahra Jamshidi (Journal of Education and Health Promotion)
Background: Novice nurses comprise a significant number of health personnel who are working in health systems. The significance of acquiring professional competence by nurses entering the hospital will ensure results such as professionalizing and giving quality services. This study aimed to explain the needs, facilitating and inhibiting factors of novice nurses’ professional competence. Materials and Methods: This qualitative study was done using a conventional content analysis method at Shiraz University of Medical Sciences, Iran, in 2021–2022. The study participants included 15 novice nurses, supervisors, head nurses, and nurses in the departments where novice nurses operate. Participants were selected purposefully. Data were collected through 17 sessions of deep and semistructured interviews and 16 sessions of semistructured field observations until data saturation was reached. Results: Following data analysis, 2570 initial codes were extracted forming four subcategories, two categories, and one theme. The theme of the present study entitled “on the path to becoming a professional” included two categories “strengthening professional skills” and “committed adherence to the profession.” Conclusion: The concept of professional competence in novice nurses occurred through on the path to becoming a professional. This concept included strengthening professional skills and committed adherence to the profession. Policymakers and educational planners of nursing education can use the results of this study to get acquainted with this concept and develop policies and guidelines to develop professional competence. By getting familiar with the concept of novice nurses’ professional competence, facilitating and inhibiting factors can educate competent nurses.